2013
DOI: 10.1111/ipd.12088
|View full text |Cite
|
Sign up to set email alerts
|

Oral health survey of 6–12‐year‐old children with disabilities attending special schools in Chennai, India

Abstract: This study gives sufficient evidence to suggest that the oral health status of this disabled population was poor and there was an increased unmet dental treatment needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 15 publications
4
18
0
4
Order By: Relevance
“…[12][13][14] Untreated gingival disease may result in chronic inflammation-induced periodontitis, a condition commonly affecting certain groups of individuals with ID such as those with Down syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] Untreated gingival disease may result in chronic inflammation-induced periodontitis, a condition commonly affecting certain groups of individuals with ID such as those with Down syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…[15] It is also similar to that reported in some lower-middleincome economies in children with ID, with the exception of Nigeria, where caries was uncommon. [14,16] Children with ID are at a higher risk of developing dental caries than the general population. [17] The type of school they attend, the diet they follow and the severity of their ID are factors that may contribute to the burden of poor oral health.…”
Section: Discussionmentioning
confidence: 99%
“…Apesar da necessidade de um acompanhamento odontológico adequado, a OMS (Organização Mundial da Saúde) relata que apenas 3% da população total de deficientes tem acesso aos tratamentos odontológicos. Corroborando com esta informação, estudos revelam que as crianças com comprometimento físico ou mental mais severo têm ainda menos acesso aos serviços odontológicos 2,5 . Isto ocorre devido à desinformação e à falta de comprometimento dos responsáveis, ao custo do tratamento, à presença de barreiras arquitetônicas, que dificultam o acesso aos serviços, e à ausência de capacitação profissional e grupos de estudo que discutam métodos facilitadores de prevenção e tratamento odontológico voltado para esses pacientes [5][6][7] .…”
Section: Introductionunclassified
“…Studies have revealed that children with a disability have worse oral health and greater treatment needs than healthy children [48]. Caries and the premature loss of deciduous teeth may lead to malocclusion in the permanent dentition [9].…”
Section: Introductionmentioning
confidence: 99%